Migration, isolation and hybridization in island crop populations: the case of Madagascar rice - Mather, Kristie A.; Molina, Jeanmaire; Flowers, Jonathan M.; Rubinstein, Samara; Rauh, Brad L.; LAWTON-RAUH, AMY; Caicedo, Ana L.; McNally, Kenneth L.; Purugganan, Michael D. (Wiley, 2010)
Understanding how crop species spread and are introduced to new areas provides insights into the nature of species range expansions. The domesticated species Oryza sativa or Asian rice is one of the key domesticated crop species in the world. The island of Madagascar off the coast of East Africa was one of the last major Old World areas of introduction of rice after the domestication of this crop species and before extensive historical global trade in this crop. Asian rice was introduced in Madagascar from India, the Malay Peninsula and Indonesia approximately 800–1400 years ago. Studies of domestication traits characteristic of the two independently domesticated Asian rice subspecies, indica and tropical japonica, suggest two major waves of migrations into Madagascar. A population genetic analysis of rice in Madagascar using sequence data from 53 gene fragments provided insights into the dynamics of island founder events during the expansion of a crop species’ geographic range and introduction to novel agro‐ecological environments. We observed a significant decrease in genetic diversity in rice from Madagascar when compared to those in Asia, likely the result of a bottleneck on the island. We also found a high frequency of a unique indica type in Madagascar that shows clear population differentiation from most of the sampled Asian landraces, as well as differential exchange of alleles between Asia and Madagascar populations of the tropical japonica subspecies. Finally, despite partial reproductive isolation between japonica and indica, there was evidence of indica/japonica recombination resulting from their hybridization on the island.